Toner and method for producing the same

JP7651340B2Active Publication Date: 2025-03-26CANON KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021051659
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-06
Filing Date
2021-03-25
Publication Date
2025-03-26
Estimated Expiration
2041-03-25

Smart Images

  • Figure 0007651340000010
    Figure 0007651340000010
  • Figure 0007651340000001
    Figure 0007651340000001
  • Figure 0007651340000002
    Figure 0007651340000002
Patent Text Reader

Abstract

To provide a toner that has satisfactory thin line reproducibility even in printing over a long period regardless of a use environment, can reduce image fogging and member contamination, and can stably obtain a high-quality image, and a method for manufacturing the toner.SOLUTION: A toner has a toner particle containing a binder resin. The binder resin contains resin A and resin B. The toner particle has convex parts on its surface. The convex parts include the resin B. The shape factor SF-2 of the toner observed by a scanning electron microscope is 105 to 120. The surface unevenness index of the toner that is observed by the scanning electron microscope and calculated by the following formula (1) is 0.010 to 0.050. (1) The surface unevenness index=(the area of an area surrounded by convex closures of the toner-the projected area of the toner) / (the projected area of the toner).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used to form a toner image by developing an electrostatic latent image formed by a method such as electrophotography, electrostatic recording, or toner jet recording, and a method for producing the toner. [Background technology]

[0002] As electrophotographic technology used in copiers, printers, facsimile receiving devices, etc. develops, the demands of users are becoming stricter year by year. In recent years, the market has expanded and the environments in which it is used have expanded, so there is a strong demand for stable image quality that is not dependent on the environment. There is also a strong demand for compact designs that can print for a long period of time. In order to satisfy the above requirements, the electrophotographic process must have (1) no change in developability (high durability), and (2) the latent image must be transferred onto the recording medium without being disturbed (high transferability). Therefore, toners are required to have both high durability and high transferability, and many improvements have been made to solve the above problems. From the viewpoint of high transferability, the shape of the toner particles is controlled to control the adhesive force between the toner and the transfer member. For example, Patent Documents 1 to 3 disclose toners in which the shape factor SF-2 of the toner particles is controlled. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-013732 A [Patent Document 2] JP 2011-197160 A [Patent Document 3] JP 2013-064965 A Summary of the Invention [Problem to be solved by the invention]

[0004] In Patent Document 1, toner particles are produced by a normal suspension polymerization method, and therefore a toner that is close to a perfect sphere is obtained. Since such a toner is likely to roll in a developing machine, the toner tends to be excessively charged, particularly in a low-temperature, low-humidity environment, and the charge amount tends to be too high. As a result, in the latter half of a long period of continuous use, the adhesive force between the toner and the toner carrier that supplies the toner becomes strong, and a large amount of residual toner remains on the carrier. If new toner is supplied onto the carrier in this state, the toner on the carrier is difficult to regulate, and image fogging and member contamination may occur. In Patent Documents 2 and 3, pulverized toner is mechanically sphericalized or particles of a certain size are aggregated to form toner particles, so the toner particles have a wide range of surfaces, from extremely uneven to round. This can cause variations in thin line reproducibility. In addition, when toner particles of such a wide range of shapes are mixed, the fluidity differs depending on the shape of the toner, so the charge amount of toner with high fluidity tends to increase, while the charge amount of toner with low fluidity tends not to increase. As a result, the charge amount distribution of the toner tends to become broad, which can cause image fogging and member contamination. As described above, there is still room for improvement in all of the toners disclosed in Patent Documents 1 to 3. Therefore, the present disclosure provides a toner that has good fine line reproducibility and reduces image fog and component contamination even in long-term printing regardless of the usage environment, and that can stably produce high-quality images, and a method for manufacturing the toner. [Means for solving the problem]

[0005] The present disclosure relates to A toner having toner particles containing a binder resin, The binder resin contains resin A and resin B, The resin A contains a styrene (meth)acrylic resin, The resin B contains a polyester resin, The acid value of the resin B is 14 mgKOH / g or more and 20 mgKOH / g or less, the toner particles have convex portions on their surfaces, The convex portion contains resin B, the toner has a shape factor SF-2 observed by a scanning electron microscope of 105 to 120; A toner characterized in that the surface unevenness index of the toner, which is calculated by the following formula (1) when observed with a scanning electron microscope, is 0.010 to 0.050: About . Surface roughness index = (area of ​​the region enclosed by the convex hull of the toner - projected area of ​​the toner) / projected area of ​​the toner (1)

[0006] The present disclosure also provides A method for producing a toner having toner particles containing a binder resin, comprising the steps of: The binder resin contains resin A and resin B, the toner particles have convex portions on their surfaces, The convex portion contains resin B, the toner has a shape factor SF-2 observed by a scanning electron microscope of 105 to 120; the toner has a surface unevenness index of 0.010 to 0.050 as calculated by the following formula (1) when observed with a scanning electron microscope; The production method comprises the steps of: A step (I) of forming particles of a polymerizable monomer composition containing a polymerizable monomer capable of forming the resin A and the resin B in an aqueous medium; a step (II) of polymerizing the polymerizable monomer contained in the particles of the polymerizable monomer composition in the aqueous medium to form resin particles; and (III) a step of maintaining the resin particles in an aqueous medium having a pH higher than the acid dissociation constant pKa of the resin B at a temperature equal to or higher than the glass transition temperature of the resin B; A method for producing a toner, comprising: Surface roughness index = (area of ​​the region enclosed by the convex hull of the toner - projected area of ​​the toner) / projected area of ​​the toner (1) Effect of the Invention

[0007] According to the present disclosure, it is possible to provide a toner and a method for manufacturing the toner that have good fine line reproducibility, reduce image fog and component contamination, and can stably produce high-quality images even in long-term printing regardless of the usage environment. [Brief description of the drawings]

[0008] [Figure 1] Schematic diagram showing the surface of a toner particle DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In the present disclosure, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified. When numerical ranges are stated in stages, the upper and lower limits of each numerical range can be combined in any way. (Meth)acrylic acid refers to acrylic acid, methacrylic acid, and acrylic acid and methacrylic acid. Similarly, (meth)acrylic acid ester means acrylic acid ester, methacrylic acid ester, and acrylic acid ester and methacrylic acid ester. "Monomer unit" refers to the reacted form of a monomeric substance in a polymer. In the main chain formed by polymerizing the vinyl monomer, one section of carbon-carbon bond is regarded as one unit. The vinyl monomer can be represented by the following formula (Z).

[0010] [ka]

[0011] In the formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), R Z2 represents an optional substituent.

[0012] Hereinafter, embodiments of the present disclosure will be described in detail, but the present disclosure is not limited to these. The toner has toner particles containing a binder resin, The binder resin contains resin A and resin B, the toner particles have convex portions on their surfaces, The convex portion contains resin B, the toner has a shape factor SF-2 observed by a scanning electron microscope of 105 to 120; The toner is characterized in that the surface unevenness index of the toner, as calculated by the following formula (1) when observed with a scanning electron microscope, is 0.010 to 0.050. Surface roughness index = (area of ​​the region enclosed by the convex hull of the toner - projected area of ​​the toner) / projected area of ​​the toner (1)

[0013] As a result of intensive research, the inventors have found that by satisfying the above-mentioned constitution, a toner having excellent transferability and an optimal charge amount can be obtained. As a result, by using the toner, even in long-term printing regardless of the usage environment, fine line reproducibility is good, image fog and member contamination are reduced, and high-quality images can be obtained stably. The inventors speculate as follows about the cause of the effect.

[0014] In order to achieve excellent fine line reproducibility, it is necessary to improve the transfer efficiency, and therefore it is preferable for the toner to have few contact points. Therefore, the shape factor SF-2 of the toner observed with a scanning electron microscope is 105 to 120. The shape factor SF-2 of the toner is preferably 107 to 118, and more preferably 110 to 116. When the shape factor SF-2 is less than 105, the charge amount tends to increase too much, and image fog tends to occur easily. On the other hand, when the shape factor SF-2 is more than 120, thin line reproducibility tends to decrease. The shape factor SF-2 is calculated by the following formula: SF-2=(projected perimeter of toner)2 / (projected area of ​​toner) / 4π×100. That is, the shape factor SF-2 is the ratio, expressed as a percentage, of the projected area of ​​a toner particle to the projected area of ​​a circular particle having the same perimeter as that of the toner particle.

[0015] On the other hand, in order to optimize the charge amount of the toner, it is necessary to make the charge amount distribution sharp while not increasing the charge amount too much. In order to prevent the charge amount of the toner from increasing too much, it is necessary to moderately reduce the fluidity of the toner, and therefore the roundness of the toner. Furthermore, in order to make the charge distribution of the toner sharp, it is important that the fluidity of each toner particle is uniform, that is, that the shape of the toner particles is uniform.

[0016] Here, even toner particles having the same shape factor SF-2 may have different surface shapes. That is, a toner particle having an extremely uneven surface and a toner particle having a large number of small particles adhering thereto may have the same shape factor SF-2 value. In such a case, since the toner particles are not uniform in shape, the toner particles that roll easily tend to have a high charge amount, while the toner particles that roll poorly tend to have a low charge amount. Therefore, the charge amount distribution of the toner tends to be broad. When the charge amount distribution becomes broad, image fogging and member contamination are likely to occur. In order to eliminate the variation in the shape of the toner, it is necessary to take into consideration the surface unevenness index represented by the following formula (1) in addition to the shape factor SF-2. Surface roughness index = (area of ​​the region enclosed by the convex hull of the toner - projected area of ​​the toner) / projected area of ​​the toner (1)

[0017] A specific analysis method will be described later, but unlike the shape factor SF-2, the surface unevenness index is a numerical representation of the degree of unevenness of the toner surface. Therefore, even if the toner has the same shape factor SF-2, the surface unevenness index can be used to distinguish whether the toner surface has many small unevennesses, only a few extreme depressions, or a large number of small particles attached thereto.

[0018] The toner of the present disclosure has a large number of small irregularities on the surface thereof, thereby improving image fog that accompanies broadening of the toner charge amount while maintaining fine line reproducibility. That is, the surface unevenness index of the toner observed under a scanning electron microscope and calculated by the above formula (1) is 0.010 to 0.050. When the surface unevenness index is less than 0.010, the toner surface does not have adequate unevenness, so the toner is excessively charged. Therefore, image fogging is likely to occur during long-term continuous use. On the other hand, when the surface unevenness index is more than 0.050, the toner surface is expected to have extreme depressions and adhesion of fine particles, so that the reproducibility of fine lines is likely to decrease and the charge distribution of the toner is likely to become broad. Therefore, image fogging and member contamination are likely to occur. The surface unevenness index is preferably from 0.015 to 0.045, and more preferably from 0.024 to 0.040.

[0019] From the viewpoint of further improving the above-mentioned effects, the standard deviation of the surface unevenness index of the toner is preferably 0.010 or less, and more preferably 0.005 or less.

[0020] From the viewpoint of further improving the above-mentioned effects, the shape factor SF-1 of the toner observed with a scanning electron microscope is preferably 105 or more. On the other hand, from the viewpoint of improving the above-mentioned effects, as well as preventing fogging on paper due to reversal fogging in a high temperature and high humidity environment, and improving adhesion to the blade of a developing machine, the shape factor SF-1 is preferably 120 or less, and more preferably 112 or less. The shape factor SF-1 is a shape factor calculated by the following formula: SF-1=(maximum projected length of toner)2 / (projected area of ​​toner)×(π / 4)×100.

[0021] The toner has toner particles containing a binder resin, the binder resin containing resin A and resin B, the toner particles have convex portions on the surface, and the convex portions contain resin B. The resin B may form the convex portions on the surface of the toner particles. From the viewpoint of satisfying the numerical range of the shape factor SF-2 and the surface unevenness index calculated by the formula (1), it is preferable to incorporate resin A and resin B into the binder resin forming the toner particles, form convex portions on the surfaces of the toner particles, and incorporate resin B into the convex portions. In addition, resin B may form convex portions on the surfaces of the toner particles. Figure 1 is a schematic diagram showing the state of the surface of a toner particle. In the figure, 1 represents resin B and 2 represents resin A.

[0022] From the viewpoint of ease of production, it is preferable that resin A contains a styrene (meth)acrylic resin, and resin B contains a polyester resin. That is, it is preferable that the convex portions on the toner particle surface contain a polyester resin, and the concave portions other than the convex portions on the toner particle surface contain a styrene (meth)acrylic resin. Furthermore, when the content of the polyester resin relative to 100.0 parts by mass of the polymerizable monomer that can form Resin A is 3.0 parts by mass or more and 15.0 parts by mass or less, or when the content of the polyester resin relative to 100.0 parts by mass of Resin A is 3.0 parts by mass or more and 15.0 parts by mass or less, it is preferable because this allows a large number of protrusions and recesses to be present, and when the content of the polyester resin relative to 100.0 parts by mass of Resin A is 3.0 parts by mass or more and 10.0 parts by mass or less, it is more preferable because this allows a large number of protrusions and recesses to be present uniformly.

[0023] The toner particles contain wax, and when the area percentage of the wax present in the region surrounded by the contour of the toner and a line 1.0 μm inward from the contour in a cross section of the toner observed under a transmission electron microscope is As, and the area percentage of the wax present in the internal region inside the line 1.0 μm inward from the contour of the toner is Ac, it is preferable that As and Ac satisfy the following formula (2). It is more preferable that they satisfy the following formula (2)'. The area percentage of the wax can be controlled within a predetermined range by appropriately adjusting the manufacturing conditions of the toner, as described later. 50.0≧[As / (Ac+As)]×100≧3.0 (2) 20.0≧[As / (Ac+As)]×100≧5.0 (2)' When the [As / (Ac+As)]×100 is within the above range, it is possible to suppress contamination of members caused by wax and toner melting while maintaining fixability.

[0024] The toner production method will be described below, but is not limited to the above. The method for producing a toner according to the present disclosure includes: A method for producing a toner having toner particles containing a binder resin, comprising the steps of: The binder resin contains resin A and resin B, the toner particles have convex portions on their surfaces, The convex portion contains resin B, the toner has a shape factor SF-2 observed by a scanning electron microscope of 105 to 120; the toner has a surface unevenness index of 0.010 to 0.050 as calculated by the following formula (1) when observed with a scanning electron microscope; The production method comprises the steps of: A step (I) of forming particles of a polymerizable monomer composition containing a polymerizable monomer capable of forming the resin A and the resin B in an aqueous medium; a step (II) of polymerizing the polymerizable monomer contained in the particles of the polymerizable monomer composition in the aqueous medium to form resin particles; and (III) a step of maintaining the resin particles in an aqueous medium having a pH higher than the acid dissociation constant pKa of the resin B at a temperature equal to or higher than the glass transition temperature of the resin B; A method for producing a toner, comprising: Surface roughness index = (area of ​​the region enclosed by the convex hull of the toner - projected area of ​​the toner) / projected area of ​​the toner (1)

[0025] When the above suspension polymerization is carried out, in an aqueous medium, the orientation of resin B to the interface of toner particles changes significantly around the acid dissociation constant pKa of resin B. In other words, when a process related to suspension polymerization is carried out in an aqueous medium having a pH higher than the acid dissociation constant pKa of resin B, resin B is likely to migrate to the interface. Therefore, in order to make the resin B unevenly distributed on the surface of the toner particles, the resin obtained by polymerization is The particles are preferably held in an aqueous medium having a pH higher than the acid dissociation constant pKa of resin B. In addition, with respect to (pH of the aqueous medium) and (acid dissociation constant pKa of resin B), the value of (pH of the aqueous medium)-(acid dissociation constant pKa of resin B) is preferably 1.3 to 5.0, and more preferably 3.5 to 4.5. Furthermore, since resin B is a polymer, the molecular movement in the toner particles is slow. Therefore, in an aqueous medium having a pH higher than the acid dissociation constant pKa of resin B, the temperature is maintained at or above the glass transition temperature (Tg) of resin B. This allows resin B to be actively distributed unevenly on the surface of the toner particles. As a result, when the toner particles have convex portions on their surfaces, resin B can be included in the convex portions. Also, convex portions due to resin B can be formed on the surface of the toner particles. Moreover, the maintaining temperature is preferably a temperature of glass transition temperature (Tg) of resin B+10°C or higher, more preferably a temperature of glass transition temperature (Tg) of resin B+15°C or higher. The upper limit of the maintaining temperature is not particularly limited, but is about a temperature of glass transition temperature (Tg) of resin B+30°C or lower. The retention time is preferably 30 minutes or more and 6 hours or less, and more preferably 1 hour or more and 5 hours or less, from the viewpoint of partially and actively distributing resin B on the surface. By increasing the retention time, the surface unevenness index value can be increased. In addition, it is preferable that the pH of the aqueous medium in the steps prior to the retaining step (III), i.e., in step (I) and / or step (II), is lower than the acid dissociation constant pKa of resin B, from the viewpoint of appropriately distributing resin B on the surface of the toner particles.

[0026] From the viewpoint of ease of production, for example, resin B that is contained in the convex portions on the surfaces of the toner particles or that is used to form the convex portions on the surfaces of the toner particles preferably contains a polyester resin. When suspension polymerization is carried out as described above, the polyester resin has a carboxy group, so that the orientation of the toner particles to the interface changes significantly around the acid dissociation constant pKa of the polyester resin in an aqueous medium. In other words, when an aqueous medium having a pH higher than the acid dissociation constant pKa of the polyester resin is maintained at a temperature equal to or higher than the glass transition temperature of the polyester resin, the polyester resin is likely to migrate to the interface. Therefore, in order to cause the polyester resin to be unevenly distributed on the surface of the toner particles, it is advisable to set the pH of the aqueous medium in the step (III) higher than the acid dissociation constant pKa of the polyester resin. Furthermore, since polyester resin is a polymer, molecular movement within the toner particles is slow. Therefore, by maintaining the temperature at or above the glass transition temperature (Tg) of the polyester resin, the polyester resin can be actively distributed unevenly on the surface of the toner particles. As a result, protrusions made of polyester resin can be formed on the surface of the toner particles.

[0027] Specifically, when a polyester resin having an acid dissociation constant pKa of less than 6.5 is used as resin B, the pH of the aqueous medium in step (III) is adjusted to 6.5 to 10.0 and maintained at a temperature equal to or higher than the glass transition temperature (Tg) of the polyester resin. The retention time is preferably 30 minutes to 6 hours, and more preferably 1 hour to 5 hours, from the viewpoint of partially and actively distributing the polyester resin on the surface. In addition, it is preferable from the viewpoint of bringing the polyester resin to the surface appropriately that the pH of the aqueous medium in the step prior to the retaining step (III), i.e., in step (I) and / or step (II), is lower than the acid dissociation constant pKa of the polyester resin.

[0028] Resin B preferably has an acid value of 10 mgKOH / g or more, more preferably 14 mgKOH / g or more, while the acid value is preferably 20 mgKOH / g or less. When the acid value of resin B is 10 mgKOH / g or more, the acid dissociation portion increases, so resin B is more likely to be distributed unevenly on the surface of the toner particles. From the viewpoint of suppressing the occurrence of yellowing, it is preferably 20 mgKOH / g or less.

[0029] Resin A preferably contains a vinyl resin, more preferably contains a styrene (meth)acrylic resin. Also, it is preferable that Resin A contains a styrene (meth)acrylic resin and Resin B contains a polyester resin, and it is more preferable that Resin A is a styrene (meth)acrylic resin and Resin B is a polyester resin. Furthermore, when the content of the polyester resin relative to 100.0 parts by mass of the polymerizable monomer capable of forming Resin A is 3.0 parts by mass or more and 15.0 parts by mass or less, or when the content of the polyester resin relative to 100.0 parts by mass of Resin A is 3.0 parts by mass or more and 15.0 parts by mass or less, it is preferable since this allows a large number of protrusions and recesses to be present, and when the content is 3.0 parts by mass or more and 10.0 parts by mass or less, it is more preferable since this allows a large number of protrusions and recesses to be present uniformly.

[0030] The vinyl resin refers to a resin obtained by radical polymerization of a monomer having a vinyl group (hereinafter also simply referred to as a "vinyl group monomer"). The vinyl resin may be a homopolymer obtained by polymerizing one type of vinyl group monomer, or a copolymer obtained by polymerizing two or more types of vinyl group monomers. Examples of the vinyl resin include homopolymers of monomers such as monomers having a styrene skeleton (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), monomers having a (meth)acrylic acid ester skeleton (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), monomers having an ethylenically unsaturated nitrile skeleton (e.g., acrylonitrile, methacrylonitrile, etc.), monomers having a vinyl ether skeleton (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), monomers having a vinyl ketone skeleton (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and monomers having an olefin skeleton (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers in combination.

[0031] The styrene (meth)acrylic resin is preferably a resin obtained by copolymerizing a monomer having a styrene skeleton and a monomer having a (meth)acrylic acid ester skeleton. The styrene (meth)acrylic resin is preferably a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth)acryloyl group. As described above, "(meth)acrylic acid" includes both "acrylic acid" and "methacrylic acid". In addition, "(meth)acryloyl group" includes both "acryloyl group" and "methacryloyl group".

[0032] Examples of monomers having a styrene skeleton (hereinafter also referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more kinds. Of these, as the styrene-based monomer, styrene is preferred from the viewpoints of ease of reaction, ease of reaction control, and availability.

[0033] Examples of monomers having a (meth)acryloyl group (hereinafter also referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters. (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, amyl (meth)acrylate, neopentyl (meth)acrylate, Examples of the (meth)acrylic acid monomer include isohexyl acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, etc.), (meth)acrylic acid aryl esters (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, t-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, and (meth)acrylamide. The (meth)acrylic acid monomer may be used alone or in combination of two or more.

[0034] The polymerizable monomer described below is preferably a copolymer of a monomer having a styrene skeleton (styrene-based monomer) and a monomer having a (meth)acrylic acid ester skeleton ((meth)acrylic monomer), from the viewpoint of partially presenting the polyester resin on the surface of the toner particles. The copolymerization ratio of the styrene monomer to the (meth)acrylic monomer (mass basis, styrene monomer / (meth)acrylic monomer) is preferably, for example, 85 / 15 to 70 / 30.

[0035] The polyester resin is preferably a non-crystalline polyester resin. If the resin is an amorphous polyester resin, it can further impart heat-resistant storage stability. Whether or not the resin is an amorphous resin can be determined by whether or not it has a melting point using a DSC measuring device. The polyester resin is preferably a condensation polymer of a polyhydric alcohol and a polycarboxylic acid. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, diethylene glycol, triethylene glycol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, cyclohexanedimethanol, butenediol, octenediol, cyclohexene dimethanol, isosorbide, hydrogenated bisphenol A, an ethylene oxide adduct of bisphenol A, and a propylene oxide adduct of bisphenol A. Examples of polyvalent carboxylic acids include benzenedicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and phthalic anhydride, and their anhydrides; and alkyldicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, and their anhydrides.

[0036] The content of the resin A in the binder resin is preferably 80% by mass to 98% by mass, and more preferably 90% by mass to 95% by mass. The content of the resin B in the binder resin is preferably 2% by mass to 20% by mass, and more preferably 4% by mass to 10% by mass. The content ratio of resin A to resin B (mass basis, resin A / resin B) is preferably 5-50, and more preferably 10-30.

[0037] The toner production method will be described in more detail below, but is not limited thereto. The toner production method includes the following steps: A step (I) of forming particles of a polymerizable monomer composition containing a polymerizable monomer capable of forming a resin A and a resin B in an aqueous medium; A step (II) of polymerizing the polymerizable monomer contained in the particles of the polymerizable monomer composition in an aqueous medium to form resin particles; and The method includes a step (III) of holding the obtained resin particles in an aqueous medium having a pH higher than the acid dissociation constant pKa of resin B at a temperature equal to or higher than the glass transition temperature of resin B.

[0038] In step (I), the polymerizable monomer composition contains a polymerizable monomer capable of forming a resin A and a resin B, and, if necessary, additives such as a colorant, a wax, a polymerization initiator, a charge control agent, a chain transfer agent, a polymerization inhibitor, and a crosslinking agent. The obtained polymerizable monomer composition is dispersed in an aqueous medium, and particles of the polymerizable monomer composition containing a polymerizable monomer capable of forming resin A, resin B, and the like are formed. The aqueous medium preferably contains poorly water-soluble inorganic fine particles as a dispersant.

[0039] The aqueous medium containing poorly water-soluble inorganic fine particles can be composed by containing poorly water-soluble inorganic fine particles and an aqueous medium containing water. In addition to the poorly water-soluble inorganic fine particles, the aqueous medium can contain counter ions generated when the poorly water-soluble inorganic fine particles are produced, and acids (e.g., hydrochloric acid and sulfuric acid) and alkalis (e.g., sodium hydroxide and sodium carbonate) added for pH adjustment.

[0040] The water used to prepare the aqueous medium may be, for example, ion-exchanged water. The aqueous medium is preferably prepared using 100 parts by mass or more of water per 100 parts by mass of the polymerizable monomer. If the amount of water used is 100 parts by mass or more, oil droplets (particles of the polymerizable monomer composition) can be easily formed without causing oil-water inversion.

[0041] The poorly water-soluble inorganic fine particles play a role as a dispersion stabilizer for the particles of the polymerizable monomer composition present in the aqueous medium. Here, the poorly water-soluble inorganic fine particles are, for example, those having extremely low solubility in water (measurement temperature: 60°C) in a specific pH range (e.g., 4.0 to 10.0) and having a number-average particle size of 1.0 μm or less. On the other hand, as the dispersion stabilizer, inorganic and organic dispersion stabilizers are known, and inorganic dispersion stabilizers are preferred. Note that an organic dispersion stabilizer (e.g., a surfactant) may be used in combination.

[0042] Examples of poorly water-soluble inorganic fine particles include calcium phosphate, magnesium phosphate, aluminum phosphate, zinc phosphate, magnesium carbonate, calcium carbonate, calcium hydroxide, magnesium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, bentonite, silica, and alumina. Among these, calcium phosphate is preferably used because of the ease of controlling the particle size. These poorly water-soluble inorganic fine particles may be used alone or in combination.

[0043] When preparing an aqueous medium containing poorly water-soluble inorganic fine particles, a commercially available dispersion stabilizer may be used as it is to disperse poorly water-soluble inorganic fine particles in water. However, in order to obtain poorly water-soluble inorganic fine particles having a fine and uniform particle size, poorly water-soluble inorganic fine particles may be generated and prepared in water under high-speed stirring. For example, when calcium phosphate is used as the poorly water-soluble inorganic fine particles, it can be prepared as follows: That is, an aqueous solution of sodium phosphate and an aqueous solution of calcium chloride are mixed under high speed stirring at a low temperature range of 60° C. or less to form calcium phosphate fine particles in water. By this, poorly water-soluble inorganic fine particles can be obtained.

[0044] Next, the polymerizable monomer composition is dispersed in an aqueous medium containing poorly water-soluble inorganic fine particles to granulate the polymerizable monomer composition particles, thereby obtaining a dispersion containing the poorly water-soluble inorganic fine particles acting as a dispersion stabilizer and the polymerizable monomer composition particles. When forming particles of the polymerizable monomer composition, it is advisable to use a stirring device such as TK Type Homomixer (trade name, manufactured by Tokushu Kika Kogyo Co., Ltd.).

[0045] The step (II) is a step of polymerizing the polymerizable monomer contained in the obtained particles of the polymerizable monomer composition in an aqueous medium to form resin particles. In the polymerization, as a polymerization initiator, either or both of an oil-soluble polymerization initiator and a water-soluble polymerization initiator can be used. Examples of the oil-soluble polymerization initiator include the following. Nitrile-based polymerization initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile; and peroxide-based polymerization initiators such as acetylcyclohexylsulfonyl peroxide, diisopropyl peroxycarbonate, decanonyl peroxide, lauroyl peroxide, stearoyl peroxide, propionyl peroxide, acetyl peroxide, t-butyl peroxy-2-ethylhexanoate, benzoyl peroxide, t-butyl peroxypivalate, t-butyl peroxyisobutyrate, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, and cumene hydroperoxide.

[0046] Examples of the water-soluble polymerization initiator include the following. Ammonium persulfate, potassium persulfate, 2,2'-azobis(N,N'-dimethyleneisobutyromidine) hydrochloride, 2,2'-azobis(2-aminodinopropane) hydrochloride, azobis(isobutylamidine) hydrochloride, 2,2'-azobisisobutyronitrile sodium sulfonate, ferrous sulfate, or hydrogen peroxide. The amount of the polymerization initiator added is preferably 0.1 to 20 parts by mass, more preferably 0.1 to 15 parts by mass, relative to 100 parts by mass of the polymerizable monomer, from the viewpoints of polymerization efficiency and safety. The polymerization initiator may be used alone or in combination of two or more types, with reference to the 10-hour half-life temperature.

[0047] In order to enhance the stress resistance of the toner particles and to control the molecular weight of the constituent molecules of the toner particles, a crosslinking agent can be used during polymerization of the polymerizable monomer. As the crosslinking agent, a compound having two or more polymerizable double bonds can be used. Specific examples of the vinyl monomer include aromatic divinyl compounds such as divinylbenzene and divinylnaphthalene; carboxylic acid esters having two double bonds such as ethylene glycol diacrylate, ethylene glycol dimethacrylate and 1,3-butanediol dimethacrylate; divinyl compounds such as divinylaniline, divinyl ether, divinyl sulfide and divinyl sulfone; and compounds having three or more vinyl groups. The crosslinking agent may be used alone or in combination of two or more kinds. The amount of the crosslinking agent added is preferably 0.05 to 10 parts by mass, and more preferably 0.10 to 5 parts by mass, relative to 100 parts by mass of the polymerizable monomer, from the viewpoint of the fixing property and offset resistance of the toner.

[0048] In order to control the degree of polymerization of the polymerizable monomer, a chain transfer agent and a polymerization inhibitor are used. It is also possible. Examples of the chain transfer agent that can be used include α-methylstyrene dimer, t-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, carbon tetrachloride, and carbon tetrabromide. Examples of the polymerization inhibitor that can be used include quinone compounds such as p-benzoquinone, chloranilyl, anthraquinone, phenanthroquinone, and dichlorobenzoquinone; hydroxy organic compounds such as phenol, tertiary butylcatechol, hydroquinone, catechol, and hydroxymonomethyl ether; nitro compounds such as dinitrobenzene, dinitrotoluene, and dinitrophenol; nitroso compounds such as nitrosobenzene and nitrosonaphthol; amino compounds such as methylaniline, p-phenylenediamine, N,N'-tetraethyl-p-phenylenediamine, and diphenylamine; and organic sulfur compounds such as tetraalkyluram disulfide and dithiobenzoyl disulfide.

[0049] The toner particles may contain a colorant. The colorant may be appropriately selected from colorants known in the toner field, taking into consideration the hue angle, saturation, brightness, weather resistance, OHT transparency, dispersibility in toner particles, and the like. Specifically, colorants such as black, yellow, magenta, and cyan pigments described below, and dyes, etc., may be used as necessary. The colorant may be used alone or in combination of multiple types. Furthermore, the colorant may be used in the form of a solid solution. The content of the colorant is preferably 1 to 20 parts by mass with respect to 100 parts by mass of the binder resin. In order to disperse a colorant such as a pigment in toner particles, the colorant can be used in a state of being dispersed in a solvent, and a polymerizable monomer (e.g., styrene) can also be used as the solvent.

[0050] The black colorant may be any known black colorant in the field of toner. Specific examples of black colorants include carbon black, and may also include black colorants prepared by mixing the yellow, magenta, and cyan colorants described below. The carbon black is not particularly limited, and may be, for example, carbon black obtained by a manufacturing method such as a thermal method, an acetylene method, a channel method, a furnace method, or a lamp black method. One type of carbon black may be used alone, or two or more types may be mixed and used. The carbon black may be a crude pigment, or may be a prepared pigment composition as long as it does not significantly inhibit the effect of the pigment dispersant. The number average particle size of the primary particles of the carbon black is not particularly limited, but is preferably 14 nm to 80 nm, and more preferably 25 nm to 50 nm.

[0051] As the yellow colorant, any yellow colorant known in the toner field can be used. As the pigment-based yellow colorant, for example, compounds represented by condensed polycyclic pigments, isoindolinone compounds, anthraquinone compounds, azo metal complex methine compounds, and allylamide compounds can be used.Specific examples include CI Pigment Yellow 3, 7, 10, 12, 13, 14, 15, 17, 23, 24, 60, 62, 74, 75, 83, 93, 94, 95, 99, 100, 101, 104, 108, 109, 110, 111, 117, 123, 128, 129, 138, 139, 147, 148, 150, 155, 166, 168, 169, 177, 179, 180, 181, 183, 185, 191:1, 191, 192, 193, and 199. Examples of dye-based yellow colorants include CI solvent Yellow 33, 56, 79, 82, 93, 112, 162, and 163, and CI disperse Yellow 42, 64, 201, and 211.

[0052] As the magenta colorant, any magenta colorant known in the toner field can be used. Examples of the magenta colorant that can be used include condensed polycyclic pigments, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds.Specific examples include CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, 238, 254, 269, and CI Pigment Violet 19.

[0053] As the cyan colorant, a cyan colorant known in the field of toner can be used. As the cyan colorant, for example, a phthalocyanine compound and its derivative, an anthraquinone compound, and a basic dye lake compound can be used. Specifically, CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66 can be mentioned.

[0054] The toner particles may contain a wax. Examples of the wax include aliphatic hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, microcrystalline wax, Fischer-Tropsch wax, and paraffin wax; oxides of aliphatic hydrocarbon waxes such as oxidized polyethylene wax, or block copolymers thereof; waxes mainly composed of fatty acid esters such as carnauba wax and montanic acid ester wax, and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax; saturated linear fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bismuth. Examples of the wax include saturated fatty acid bisamides such as stearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, and hexamethylene bisstearic acid amide; unsaturated fatty acid amides such as ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, N,N'dioleyl adipic acid amide, and N,N'dioleyl sebacic acid amide; aromatic bisamides such as m-xylene bisstearic acid amide and N,N'distearyl isophthalic acid amide; fatty metal salts (generally known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes obtained by grafting aliphatic hydrocarbon waxes with vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having a hydroxyl group obtained by hydrogenating vegetable oils and fats. These waxes may be used alone or in combination of two or more. Of these, aliphatic hydrocarbon waxes and monoester waxes containing linear fatty acid ester as the main component are preferred. The peak temperature (melting point) of the maximum endothermic peak of the wax measured with a differential scanning calorimeter (DSC) is preferably from 60°C to 140°C, and more preferably from 60°C to 90°C. The content of the wax is preferably 2.5 parts by mass to 25.0 parts by mass with respect to 100 parts by mass of the binder resin.

[0055] In order to keep the chargeability of the toner particles stable regardless of the environment, the toner particles may contain a charge control agent. As the charge control agent, known ones can be used. In particular, those having a high charging speed and a constant charging speed can be used. A charge control agent capable of stably maintaining the charge amount is preferred. Furthermore, when the toner particles are produced by a direct polymerization method, a charge control agent that has low polymerization inhibition and is substantially free of solubilized substances in an aqueous medium is particularly preferred. Specific compounds include negative charge control agents, such as metal compounds of aromatic carboxylic acids such as salicylic acid, alkyl salicylic acid, dialkyl salicylic acid, naphthoic acid, and dicarboxylic acid, metal salts or metal complexes of azo dyes or azo pigments, boron compounds, silicon compounds, and calixarenes. Positive charge control agents include, for example, quaternary ammonium salts, polymeric compounds having the quaternary ammonium salts in the side chains, guanidine compounds, nigrosine compounds, and imidazole compounds. The charge control agent may be used alone or in combination of two or more kinds. The charge control agent is preferably a metal-containing salicylic acid compound, the metal of which is preferably aluminum or zirconium. The preferred charge control agent is an aluminum salicylate compound. Alternatively, a resin-based charge control agent may be used, specifically, a polymer or copolymer having a sulfonic acid group, a sulfonate group, a sulfonate ester group, a salicylic acid moiety, or a benzoic acid moiety. The content of the charge control agent is preferably 0.01 parts by mass to 20 parts by mass, and more preferably 0.05 parts by mass to 10 parts by mass, relative to 100 parts by mass of the binder resin.

[0056] Step (III) is a step of holding the resin particles obtained in step (II) in an aqueous medium having a pH higher than the acid dissociation constant pKa of resin B at a temperature equal to or higher than the glass transition temperature of resin B. As described above, resin B is a polymer, and therefore molecular movement in the toner particles is slow. Therefore, by carrying out a step of holding the resin particles in an aqueous medium having a pH higher than the acid dissociation constant pKa of resin B at a temperature equal to or higher than the glass transition temperature (Tg) of resin B, resin B can be actively unevenly distributed on the surface of the toner particles. The retention time is preferably 30 minutes to 6 hours, and more preferably 1 hour to 5 hours. In addition, the pH of the aqueous medium in the step prior to the retention step (III), i.e., in step (I) and / or step (II), is preferably lower than the acid dissociation constant pKa of resin B, from the viewpoint of appropriately distributing resin B on the surface of the toner particles.

[0057] In addition, the production method may include a distillation step between steps (II) and (III). The distillation step is a step for removing volatile impurities such as unreacted polymerizable monomers and by-products. The distillation step can be carried out under normal pressure (101325 Pa) or reduced pressure (0.5 kPa to 0.95 kPa).

[0058] In addition, in the manufacturing method, after step (III), the dispersion liquid containing the resin particles can be treated with an acid or alkali in order to remove the dispersion stabilizer attached to the surface of the obtained resin particles. In this case, the resin particles are separated into a solid phase by a general solid-liquid separation method, but in order to completely remove the acid or alkali and the dispersion stabilizer dissolved therein, it is preferable to add water again to wash the resin particles. This washing is repeated several times, and after sufficient washing, it is preferable to perform solid-liquid separation again to obtain toner particles. The obtained toner particles can be dried by a known drying means if necessary.

[0059] For the purpose of imparting various properties to the toner, the obtained toner particles may have external additives on their surfaces. From the viewpoint of durability when present on the surface of toner particles, the external additive preferably has a particle size of 1 / 10 or less of the weight average particle size of the toner particles before the external additive is added. Examples of the external additive include the following: Metal oxides such as aluminum oxide, titanium oxide, strontium titanate, cerium oxide, magnesium oxide, chromium oxide, tin oxide, and zinc oxide; nitrides such as silicon nitride; carbon Carbides: Carbides such as silicon carbide; inorganic metal salts such as calcium sulfate, barium sulfate, calcium carbonate; fatty acid metal salts such as zinc stearate, calcium stearate; carbon black, silica. The content of the external additive is preferably 0.01 parts by mass to 10 parts by mass, and more preferably 0.05 parts by mass to 5 parts by mass, relative to 100 parts by mass of the toner particles. One type of external additive may be used alone, or multiple types may be used in combination. From the viewpoint of charging stability, it is preferable to use these external additives whose surfaces have been hydrophobized. Examples of the hydrophobization method include surface treatment with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, isobutyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, or hexamethylenedisilazane.

[0060] The toner can be applied to image forming methods using known one-component development methods and two-component development methods. The toner can be used in any system. For example, it can be used as a toner for a high-speed system, a toner for an oil-less fixing system, a toner for a cleaner-less system, or a toner for a development system in which carrier in a developing device that has deteriorated due to long-term use is sequentially recovered and fresh carrier is replenished.

[0061] The methods for measuring various physical properties of the toner will be described below. <Calculation of surface roughness index> The surface unevenness index of the toner is calculated by observing the toner using a scanning electron microscope, and using the measured values ​​of the obtained image, according to the following formula (1). Surface roughness index = (area of ​​the region enclosed by the convex hull of the toner - projected area of ​​the toner) / projected area of ​​the toner (1) The specific observation method and image measurement method are as follows. First, the toner was magnified 100,000 to 200,000 times using a scanning electron microscope (SEM) "S-4800" (manufactured by Hitachi, Ltd.). In the obtained field of view, an image was obtained in which the toner particles within the range of ±2.0 μm from the weight average particle size of the toner were captured individually. The obtained image is subjected to image processing so that the external additives on the toner surface can be ignored, and then binarized and image processed to calculate the surface unevenness index of the toner. The binarization conditions are appropriately selected depending on the observation device. Here, the image analysis software Image-Pro Plus5.1J (Media Cybernetics) is used for binarization. The background luminance distribution is removed from the Subtract Background menu with a flattening radius of 40 pixels, and then binarized with a luminance threshold of 50 to obtain a binarized image. The obtained binarized image is subjected to particle analysis using image analysis software Image-Pro Plus5.1J to calculate the surface unevenness index of the toner. The calculation procedure is as follows. (1) Set the scale by selecting [Analyze]-[Set Scale]. (2) [Process] → [Filters] → [Gaussian Blur] and set Sigma (Radius) to 1.7. (3) Select Huang in [Image]-[Adjust]-[Threshold], check Dark Background, and change the value so that the particles are filled in red to determine the threshold. (4) [Analyze] → [Analyze Particle], set Size(Pixel^2) to 50-Infinity and Circularity to 0.0-1.00. Check the following six items. Display Results, ClearResults, Summarize, Add to Manager, Exclude on edges, Include Holes. If you set Show to Nothing and run it, a window will be generated. The Total Area in the generated "Summary" window is the projected area of ​​the toner. It becomes. (5) Next, select [File] → [New] → [Image] and enter the Pixels displayed in the window of the particle image generated by Duplicate. (6) Select ROI Manager, select the number corresponding to the toner in ROI Manager, and confirm that a line in the shape of the toner appears in the black image part of the generated window. (7)Go to [Edit] → [Selection] → [Convex Hull]. (8)Select [Edit] → [Invert]. (9) Delete the yellow frame of the selected window (the yellow frame will disappear if you click once inside the window), and select [Edit] → [Invert] again. (10) In [Analyze] → [Analyze Particle], set Size(Pixel^2) to 5-Infinity and Circularity to 0.1-1.00. Check the following six items. Display Results, ClearResults, Summarize, Add to Manager, Exclude on edges, Include Holes. If you set Show to Nothing and run it, a window will be generated. The Total Area of ​​the generated "Summary" window is the area of ​​the region enclosed by the convex hull of the toner. The toner surface unevenness index is calculated using the above-mentioned toner projected area and the area of ​​the region surrounded by the convex hull of the toner. The above analysis is performed on 100 binarized images, and the arithmetic mean value of the obtained surface unevenness index is defined as the "toner surface unevenness index." In addition, the arithmetic mean value of the standard deviation of the surface unevenness index obtained by the measurement is defined as the "toner surface unevenness index standard deviation."

[0062] <Calculation of shape factor SF-1 and shape factor SF-2> The shape factor SF-1 and the shape factor SF-2 of the toner are calculated by the following method. The toner is observed using a scanning electron microscope (SEM) "S-4800" (manufactured by Hitachi, Ltd.). In a field of view magnified 100,000 to 200,000 times, the maximum projected length, projected area, and projected perimeter of 100 toner particles are measured using image processing software Image-Pro Plus5.1J (manufactured by Media Cybernetics), and the shape factor SF-1 and shape factor SF-2 are calculated using the following formula. The arithmetic average values ​​of the shape factor SF-1 values ​​and shape factor SF-2 values ​​of the 100 toner particles are defined as the shape factor SF-1 and shape factor SF-2. Shape factor SF-1 = (maximum projected length of toner)2 / (projected area of ​​toner) × (π / 4) × 100 Shape factor SF-2 = (projected perimeter of toner)2 / (projected area of ​​toner) / 4π×100 The calculation procedure using Image-Pro Plus 5.1J is described below. (1) Set the scale by selecting [Analyze]-[Set Scale]. (2) [Process] → [Filters] → [Gaussian Blur] and set Sigma (Radius) to 1.7. (3) Select Huang in [Image]-[Adjust]-[Threshold], check Dark Background, and change the value so that the particles are filled in red to determine the threshold. (4) [Analyze] → [Analyze Particle], set Size(Pixel^2) to 50-Infinity and Circularity to 0.0-1.00. Check the following six items. Display Results, ClearResults, Summarize, Add to Manager, Exclude on edges, Include Holes. Set "Show" to "Nothing" and execute, then a window will be generated. For the generated "Summary" window, FeretX is the projected minor axis of the toner, FeretY is the projected major axis of the toner, Perim. is the projected perimeter of the toner, and the projected area of the toner. Substitute these values into the formula to obtain SF-1 and SF-2.

[0063] <Calculation of As and Ac> The percentage of the occupied area of wax (%) As in the area surrounded by the contour of the toner and the line 1.0 μm away from the contour to the inside of the toner, and the percentage of the occupied area of wax (%) Ac in the internal area inside the line 1.0 μm away from the contour of the toner to the inside of the toner in the cross-section of the toner observed by a transmission electron microscope are calculated as follows. The wax distribution state in the toner is observed by a transmission electron microscope for the cross-section of the toner, As and Ac are calculated from the cross-sectional area of the domain formed by the wax, and evaluated by the arithmetic mean value of 10 arbitrarily selected toners. Specifically, the toner is embedded in a visible light curable embedding resin (D-800, manufactured by Nisshin EM Co., Ltd.), cut to a thickness of 60 nm by an ultrasonic ultramicrotome (EM5, manufactured by Leica), and Ru staining (RuO4 gas, stained for 15 minutes in an atmosphere of 500 Pa) is performed by a vacuum staining device (manufactured by Filgen). After that, observation is carried out at an acceleration voltage of 120 kV by a transmission electron microscope (H7500, manufactured by Hitachi). For the cross-section of the toner to be observed, 10 cross-sections within ±2.0 μm from the weight average particle diameter of the toner are selected and photographed. Using image processing software (Photoshop 5.0, manufactured by Adobe) for the obtained image, the distinction between the wax domain and the binder resin area is clarified. More specifically, the wax domains can be distinguished as follows: Using image processing software, the captured transmission electron microscope image is binarized by setting the brightness (gradation 255) threshold to 160. At this time, the wax in the toner and the visible light curable embedding resin (D-800) become bright areas, and everything other than the wax in the toner becomes dark areas. The outline of the cross section of the toner can be distinguished by the brightness of the toner and the visible light curable embedding resin. The toner cross section is masked to leave the area surrounded by the toner contour and a line 1.0 μm inward from the contour (including the area on the 1.0 μm line). In detail, a line is drawn from the center of gravity of the toner cross section to a point on the contour of the toner cross section. On the line, a position 1.0 μm from the contour in the direction of the center of gravity is specified. Then, this operation is performed for one circumference of the contour of the toner cross section to clearly indicate the area surrounded by the toner contour and a line 1.0 μm inward from the toner contour on the toner cross section. The percentage of the area occupied by the wax domain present in the area is calculated with respect to the area of ​​the obtained area and is designated as As1. This operation is performed for 10 toner particles, and the arithmetic average value of the obtained As values ​​is designated as As (area %). On the other hand, the percentage of the area occupied by the wax domains in the inner region of the area of ​​the previously masked portion, i.e., the area of ​​the inner region inside the line 1.0 μm away from the toner contour in the cross section of the toner, is calculated and designated as Ac1. This operation is carried out for 10 toner particles, and the arithmetic average value of the obtained Ac values ​​is designated as Ac (area %).

[0064] <Measurement of resin glass transition temperature (Tg)> The glass transition temperature (Tg) is measured using a differential scanning calorimeter "Q2000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, about 2 mg of resin is precisely weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference. The measurement is carried out in the temperature range of 30°C to 200°C at a temperature rise rate of 10°C / min. In the measurement, the temperature is raised to 200° C. once, then lowered to 30° C. at a rate of 10° C. / min, and then raised again. During this second temperature rise, a specific heat change is obtained in the temperature range of 40° C. to 100° C. The glass transition temperature (Tg: unit: ° C.) of the resin is determined as the temperature at the point where a straight line equidistant in the vertical direction from the straight line extending from each baseline before and after the specific heat change occurs intersects with the curve of the stepwise change in the glass transition.

[0065] <Measurement of resin softening point> The softening point of the resin (unit: °C) is measured using a constant-load extrusion type capillary rheometer "Flow Property Evaluation Device Flow Tester CFT-500D" (manufactured by Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston, and at the same time, the measurement sample filled in the cylinder is heated and melted, and the molten measurement sample is extruded from the die at the bottom of the cylinder. During this series of processes, a flow curve is obtained that shows the relationship between the piston descent amount and temperature. In the present disclosure, the "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow characteristic evaluation device Flow Tester CFT-500D" is defined as the softening point. The melting temperature in the 1 / 2 method is calculated as follows. First, 1 / 2 of the difference between the amount of piston descent Smax at the time when the outflow ends and the amount of piston descent Smin at the time when the outflow starts is calculated (this is defined as X, where X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent on the flow curve is the sum of X and Smin is the melting temperature in the 1 / 2 method. The measurement sample is prepared by compressing 1.00 g of resin at 10 MPa for 60 seconds using a tablet molding machine (NT-100H, manufactured by NPA Systems) in an environment of 25°C to form a cylindrical shape with a diameter of 8 mm. The measurement conditions for the CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm

[0066] <Measurement of resin acid value and resin acid dissociation constant pKa> The acid value of a resin means the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of a resin is measured according to JIS K 0070-1992, and the specific procedure is as follows. First, titration is performed using a 0.1 mol / L potassium hydroxide ethyl alcohol solution (Kishida Chemical Co., Ltd.). The factor of the potassium hydroxide ethyl alcohol solution is determined using a potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., potentiometric titration measuring device AT-510 (product name)). Specifically, 100 mL of 0.100 mol / L hydrochloric acid is placed in a 250 mL tall beaker and titrated with the potassium hydroxide ethyl alcohol solution, and the factor is determined from the amount of potassium hydroxide ethyl alcohol solution required for neutralization. 0.100 mol / L hydrochloric acid prepared in accordance with JIS K 8001-1998 is used. The conditions for measuring the acid value are shown below. Titrator: Potentiometric titrator AT-510 (product name, manufactured by Kyoto Electronics Manufacturing Co., Ltd.) Electrode: Composite glass electrode double junction type (Kyoto Electronics Manufacturing Co., Ltd.) Control software for titrator: AT-WIN Titration analysis software: Tview The titration parameters and control parameters during titration are set as follows: <Titration parameters> Titration mode: Blank titration Titration method: Total volume titration Maximum titer: 20mL Waiting time before titration: 30 seconds Titration direction: automatic <Control parameters> End point potential: 30dE End point potential: 50 dE / dmL End point detection judgment: Not set Control speed mode: Standard Gain: 1 Data collection potential: 4mV Data collection titration volume: 0.1mL <Actual exam> Weigh out 0.100 g of the measurement sample (resin) into a 250 mL tall beaker, add 150 mL of a mixed solution of toluene / ethanol (3:1), and dissolve for 1 hour. Using the potentiometric titration apparatus, titrate with the potassium hydroxide ethyl alcohol solution. <Blank Test> The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (3:1) mixed solution is used). The obtained results are substituted into the following formula to calculate the acid value of the resin (Av: unit: mgKOH / g). Av = [(CB) × f × 5.61] / S In the formula, Av is the acid value (mgKOH / g), B is the amount (mL) of potassium hydroxide ethyl alcohol solution added in the blank test, C is the amount (mL) of potassium hydroxide ethyl alcohol solution added in the main test, f is the factor of the potassium hydroxide ethyl alcohol solution, and S is the mass (g) of the sample (resin). Since the pKa is the same as the pH at half the amount of 0.1 mol / L potassium hydroxide ethyl alcohol solution needed to reach the neutralization point, the pH at half the amount is read from the titration curve.

[0067] <Measurement of toner particle size> To measure the particle size of the toner, a precision particle size distribution measuring device using the pore electrical resistance method (product name: Coulter Counter Multisizer 3) and dedicated software (product name: Beckman Coulter Multisizer 3 Version 3.51, manufactured by Beckman Coulter, Inc.) are used. The aperture diameter is set to 100 μm, and measurements are made with an effective number of measurement channels of 25,000, and the measurement data is analyzed. The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1 mass %, for example ISOTON II (trade name) manufactured by Beckman Coulter. Before performing measurements and analysis, the dedicated software is set up as follows. In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using standard particles (10.0 μm, Beckman Coulter). By pressing the threshold / noise level measurement button, the threshold and noise level are automatically set. Also, the current is set to 1600μA, the gain is set to 2, and the electrolyte is ISOTON II (trade name). ) and check Flush aperture tube after measurement. In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows. (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, remove dirt and air bubbles from inside the aperture tube using the "Aperture Tube Flush" function of the dedicated software. (2) About 30 mL of the aqueous electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and about 0.3 mL of a diluted solution of Contaminon N (trade name) (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments, manufactured by Wako Pure Chemical Industries, Ltd.) diluted three times by mass with ion-exchanged water is added thereto. (3) A predetermined amount of ion-exchanged water and approximately 2 mL of Contaminon N (trade name) are added to the water tank of an ultrasonic disperser (product name: Ultrasonic Dispersion System Tetora150, manufactured by Nikkaki Bios Co., Ltd.) that has two built-in oscillators with an oscillation frequency of 50 kHz and a phase shift of 180 degrees and an electrical output of 120 W. (4) The beaker (2) is set in the beaker fixing hole of the ultrasonic disperser, and the ultrasonic disperser is operated. Then, the height position of the beaker is adjusted so that the resonance state of the liquid surface of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, 10 mg of toner is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, the electrolytic solution (5) in which the toner is dispersed is dropped into the round-bottom beaker (1) placed in the sample stand, and the measurement concentration is adjusted to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) or number average particle size (D1) is calculated. Note that when the dedicated software is set to Graph / Volume %, the "Average diameter" on the "Analysis / Volume Statistics (Arithmetic Mean)" screen is the weight average particle size (D4). When the dedicated software is set to Graph / Number %, the "Average diameter" on the "Analysis / Number Statistics (Arithmetic Mean)" screen is the number average particle size (D1).

[0068] <Measurement of Average Circularity of Toner> The average circularity of the toner is measured using a flow type particle image analyzer "FPIA-3000" (manufactured by Sysmex Corporation) under the measurement and analysis conditions at the time of the calibration work. The specific measurement method is as follows. First, about 20 mL of ion-exchanged water from which impurities such as solids have been removed is placed in a glass container. About 0.2 mL of a dilution of "Contaminon N" (a 10% aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7, consisting of a nonionic surfactant, an anionic surfactant, and an organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) diluted about 3 times by mass with ion-exchanged water is added to the container as a dispersant. 0.02 g of the measurement sample is further added, and the dispersion treatment is performed for 2 minutes using an ultrasonic disperser to obtain a dispersion liquid for measurement. At that time, the temperature of the dispersion liquid is appropriately cooled so that it is 10°C or higher and 40°C or lower. As the ultrasonic disperser, a tabletop ultrasonic cleaner disperser (e.g., "VS-150" (manufactured by Vervoclear Co., Ltd.) with an oscillation frequency of 50 kHz and an electrical output of 150 W is used, a predetermined amount of ion-exchanged water is placed in the water tank, and about 2 mL of the Contaminon N is added to the water tank. For the measurement, the flow type particle image analyzer equipped with "LUCPLFLN" (magnification 20x, numerical aperture 0.40) is used as the objective lens, and particle sheath "PSE-900A" (manufactured by Sysmex Corporation) is used as the sheath liquid. The dispersion liquid prepared according to the above procedure is introduced into the flow type particle image analyzer, and 2000 toner particles are measured in HPF measurement mode and total count mode. The binarization threshold for particle analysis is set to 85%, the analyzed particle diameter is limited to a circle equivalent diameter of 1.977 μm or more and less than 39.54 μm, and the average circularity of the toner particles is measured. Find the degree. Before starting the measurement, automatic focus adjustment is performed using standard latex particles (Duke Scientific's "RESEARCH AND TEST PARTICLES Latex Microsphere Suspensions 5100A" diluted with ion-exchanged water). After that, it is preferable to perform focus adjustment every 2 hours from the start of the measurement. The flow-type particle image analyzer used was calibrated by Sysmex Corporation and has a calibration certificate issued by Sysmex Corporation. Measurements are performed under the same measurement and analysis conditions as when the calibration certificate was issued, except that the particle size to be analyzed is limited to a circular equivalent diameter of 1.977 μm or more and less than 39.54 μm. EXAMPLES

[0069] The following provides a more detailed explanation using examples and comparative examples. However, the present disclosure is not limited to the following examples and comparative examples. In the examples and comparative examples, "parts" and "%" are all by mass unless otherwise specified.

[0070] <Resin B: Production example of polyester resin 1> In a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, the acid component and the alcohol component in the amounts shown in Table 1 below were put in, and then 1.5 parts of dibutyltin were added as a catalyst relative to 100 parts of the total amount of monomers. Next, the temperature was quickly raised to 180°C under normal pressure in a nitrogen atmosphere, and then water was distilled off while heating from 180°C to 210°C at a rate of 10°C / hour to perform condensation polymerization. After reaching 210°C, the pressure in the reaction vessel was reduced to 5 kPa or less, and condensation polymerization was performed under conditions of 210°C and 5 kPa or less to obtain polyester resin 1. At that time, the polymerization time was adjusted so that the softening point of the obtained polyester resin 1 was 126°C. The physical properties of the obtained polyester resin 1 are shown in Table 1.

[0071] <Resin B: Production Examples of Polyester Resins 2 to 5> Polyester resins 2 to 5 were produced in the same manner as in Production Example of Polyester Resin 1, except that the blending amounts of the acid component and the alcohol component were changed as shown in Table 1. The physical properties of the obtained polyester resins 2 to 5 are shown in Table 1.

[0072] [Table 1] TPA: Terephthalic acid TMA: Trimellitic anhydride BPA(PO): Bisphenol A propylene oxide 2 mol adduct BPA(EO): Bisphenol A with 2 moles of ethylene oxide EG: Ethylene glycol IS: Isosorbide In the table, the unit of glass transition temperature is "°C", and the unit of acid value is "mgKOH / g".

[0073] <Toner 1 Manufacturing Example> (Preparation of aqueous medium) A granulation tank was charged with 100.0 parts of ion-exchanged water, 2.0 parts of sodium phosphate, and 0.9 parts of hydrochloric acid having a hydrogen chloride concentration of 10% by mass, and the mixture was heated and maintained at 50°C. To this, an aqueous calcium chloride solution prepared by dissolving 1.2 parts of calcium chloride hexahydrate in 8.2 parts of ion-exchanged water was added. After the addition, the mixture was stirred for 30 minutes at a peripheral speed of 25 m / s using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain an aqueous medium containing poorly water-soluble inorganic fine particles with a pH of 5.0.

[0074] (Preparation of Polymerizable Monomer Composition) (Preparation of Pigment Dispersion Composition) Styrene 39.0 parts Carbon black 6.5 parts (Nipex35, Evonik Japan) The above materials were introduced into an attritor (manufactured by Nippon Coke Corporation) and stirred at 200 rpm at 25° C. for 180 minutes using zirconia beads with a radius of 1.25 mm, and then the zirconia beads were removed to prepare a pigment dispersion composition.

[0075] (Preparation of Polymerizable Monomer Composition) The following materials were placed in a container and mixed and dispersed at a peripheral speed of 20 m / s using a TK homomixer (manufactured by Tokushu Kika Kogyo). Pigment dispersion composition 45.5 parts Styrene 33.0 parts n-Butyl acrylate 28.0 parts Polyester resin 1 5.0 parts Furthermore, after heating to 60°C, 5.0 parts of a hydrocarbon wax (melting point: temperature at which the endothermic peak is at its maximum: 77°C) and 9.0 parts of behenyl behenate wax (melting point: temperature at which the endothermic peak is at its maximum: 72°C) were added, and the mixture was dispersed and mixed for 30 minutes to obtain a polymerizable monomer composition.

[0076] <Process (I)> The polymerizable monomer composition was put into an aqueous medium containing poorly water-soluble inorganic fine particles, and stirred at a peripheral speed of 30 m / s with a TK homomixer (manufactured by Tokushu Kika Kogyo) at a temperature of 60° C. and under a nitrogen atmosphere. 6.0 parts of a polymerization initiator t-hexyl peroxypivalate (manufactured by Nippon Oil & Fats Corporation, trade name "Perhexyl PV", molecular weight: 202, 10-hour half-life temperature: 53.2° C.) was dissolved in the mixture to prepare a polymerizable monomer composition containing the polymerization initiator.

[0077] <Process (II)> The dispersion containing the particles of the polymerizable monomer composition was transferred to another tank, and the temperature was raised to 70°C while stirring with a paddle stirring blade, and the polymerizable monomer contained in the particles of the polymerizable monomer composition was polymerized for 6 hours. Thereafter, the temperature was further raised to 90°C, and the reaction was continued for 6 hours to form resin particles.

[0078] <Distillation process> After the polymerization step was completed, steam at 120°C was started to be fed to the slurry containing the aqueous medium and the resin particles at a flow rate of 30.0 parts / hr. After the start of the steam feed, distillation was started when the temperature reached 98°C, and distillation was continued for 8 hours.

[0079] <Process III> After the distillation process, a 7.0% aqueous solution of sodium carbonate was added to the slurry containing the aqueous medium and the resin particles so that the pH of the aqueous medium became 8.0, and the mixture was then kept at 80° C. for 1 hour.

[0080] <Washing, filtering, drying, and classification processes> After the step (III) was completed, the mixture was cooled, hydrochloric acid was added to adjust the pH to 1.4, and the mixture was stirred for 2 hours to obtain an aqueous dispersion containing toner particles. The toner particles were separated from the aqueous dispersion by filtration, washed with water, dried at 40° C. for 48 hours, and classified to obtain toner particles 1.

[0081] <External addition process> 0.5 parts of hydrophobic silica fine particles having a primary particle number average particle size of 20 nm and surface-treated with 25% by mass of hexamethyldisilazane were added to 100.0 parts of toner particles 1, and mixed in a Henschel mixer (FM-10 type manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 1. The temperature of the Henschel mixer was adjusted so that the temperature of the mixture was 30°C. The main formulation and manufacturing conditions of Toner 1 are shown in Table 2.

[0082] [Table 2] In the table, A is a hydrocarbon wax (melting point: the temperature at which the endothermic peak is maximum: 77°C), B is behenyl behenate (melting point: 72°C), C represents pentaerythritol stearyl ester (melting point: 72° C.).

[0083] <Production examples of toners 2 to 18> Toners 2 to 18 were obtained in the same manner as in the production example of Toner 1, except that the formulation and production conditions were changed as shown in Table 2.

[0084] <Production Example of Toner 19> <Preparation of Resin B Particle Dispersion 1> 100.0 parts of polyester resin 1 and 350 parts of ion-exchanged water were placed in a stainless steel container and melted by heating to 95° C. in a warm bath. Then, while thoroughly stirring at 7800 rpm using a homogenizer (IKA Ultra Turrax T50), 0.1 mol / L sodium bicarbonate was added to adjust the pH to more than 7.0. Thereafter, a mixed solution of 3 parts of sodium dodecylbenzenesulfonate and 300 parts of ion-exchanged water was gradually added dropwise to emulsify and disperse the mixture, thereby obtaining a polyester resin particle dispersion. The dispersion was cooled to room temperature, and ion-exchanged water was added to obtain Resin B Particle Dispersion 1 having a solid content of 12.5% ​​by mass and a volume-based median diameter of 0.2 μm.

[0085] <Preparation of Resin A Particle Dispersion 2> 78.0 parts of styrene, 20.7 parts of n-butyl acrylate, 1.3 parts of acrylic acid as a carboxyl group-imparting monomer, and 3.2 parts of n-lauryl mercaptan were mixed and dissolved. An aqueous solution containing 1.5 parts of NEOGEN RK (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 150 parts of ion-exchanged water was added to this solution and dispersed. An aqueous solution containing 0.3 parts of potassium persulfate and 10 parts of ion-exchanged water was added while slowly stirring for another 10 minutes. After nitrogen replacement, emulsion polymerization was carried out at 70°C for 6 hours. After polymerization was completed, the reaction solution was cooled to room temperature, and ion-exchanged water was added to obtain Resin A Particle Dispersion 2 having a solid content of 12.5% ​​by mass and a volume-based median diameter of 0.2 μm.

[0086] <Preparation of wax dispersion> 100 parts of a hydrocarbon wax (melting point: 77°C) and 15 parts of NEOGEN RK were mixed with 385 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 (manufactured by Jokou Co., Ltd.) to obtain a wax dispersion. The solid content of the wax dispersion was 20% by mass.

[0087] <Preparation of Colorant Dispersion> 100 parts of carbon black "Nipex35 (manufactured by Orion Engineered Carbons)" and 15 parts of Neogen RK were mixed with 885 parts of ion-exchanged water, and dispersed for about 1 hour using a wet jet mill JN100 to obtain colorant dispersion 1.

[0088] <Preparation of Toner Particles> [Particle growth process] 54 parts of resin B particle dispersion 1, 250 parts of resin A particle dispersion 2, 20 parts of wax dispersion, and 20 parts of colorant dispersion were mixed and dispersed using a homogenizer (IKA Ultra Turrax T50). The temperature inside the container was adjusted to 30°C while stirring, and a 1 mol / L aqueous sodium hydroxide solution was added to adjust the pH to 8.0 (pH adjustment 1). As a flocculant, an aqueous solution of 0.25 parts of aluminum chloride dissolved in 10 parts of ion-exchanged water was added over 10 minutes while stirring at 30°C. After leaving it for 3 minutes, the temperature was raised to 50°C to generate flocculant particles. In this state, the particle size of the flocculant particles was measured using a Coulter Counter Multisizer 3 (registered trademark, manufactured by Beckman Coulter, Inc.). When the weight average particle size reached 6.6 μm, 0.9 parts of sodium chloride and 5.0 parts of Neogen RK were added to stop particle growth.

[0089] [Spheronizing process] After adjusting the pH to 8.5 by adding 1 mol / L aqueous sodium hydroxide solution, the mixture was heated to 95° C. and the aggregated particles were spheroidized at the same temperature for 5 hours. After that, the mixture was cooled to room temperature to obtain toner particle dispersion 1.

[0090] [Washing, filtering, drying, and classification processes] Hydrochloric acid was added to the obtained toner particle dispersion 1 to adjust the pH to 1.5 or less, and the mixture was left to stir for 1 hour, and then the mixture was subjected to solid-liquid separation using a pressure filter to obtain a toner cake. This was reslurried with ion-exchanged water to make a dispersion again, and then the mixture was subjected to solid-liquid separation using the above-mentioned filter. The reslurry and solid-liquid separation were repeated until the electrical conductivity of the filtrate became 5.0 μS / cm or less, and finally the mixture was subjected to solid-liquid separation to obtain a toner cake. The obtained toner cake was dried and further classified using a classifier so that the weight average particle size became 6.0 μm, and toner particles 19 were obtained.

[0091] [External addition process] 0.5 parts of hydrophobic silica fine particles having a primary particle number average particle size of 20 nm and surface-treated with 25% by mass of hexamethyldisilazane were added to 100.0 parts of toner particles 19, and mixed in a Henschel mixer (FM-10 type manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 19. The temperature of the Henschel mixer was adjusted so that the temperature of the mixture was 30°C. Here, the production conditions of toner 19 are shown in Table 3.

[0092] [Table 3]

[0093] <Production Example of Toner 20-22> Toners 20 to 22 were obtained in the same manner as in the production example of Toner 19, except that the production conditions were changed as shown in Table 3.

[0094] <Production Example of Toner 23> Polyester resin 1 (resin B) 5.0 parts Styrene and n-butyl acrylate copolymer (Resin A) 100.0 parts (copolymerization mass ratio: styrene:n-butyl acrylate=72:28, peak molecular weight (Mp)=14000) Methyl ethyl ketone 80.0 parts Ethyl acetate 80.0 parts Hydrocarbon wax (melting point: maximum endothermic peak temperature: 77℃) 14.0 copies Carbon black 6.0 parts (Nipex35, Evonik Japan) Sodium dodecylbenzenesulfonate 0.5 parts The above materials were dispersed for 3 hours using an Attritor (manufactured by Mitsui Kinzoku Co., Ltd.), and then left to stand for 72 hours. A mixed colorant dispersion was obtained.

[0095] Separately, 0.25 parts of aluminum chloride was added to 220 parts of ion-exchanged water, which was then heated to 65°C, and 20 parts of a 1.0 mol / L CaCl2 aqueous solution was gradually added to prepare an aqueous medium. The mixed colorant dispersion was added to the aqueous medium and stirred at 65° C. under a nitrogen atmosphere at 12,000 rpm for 15 minutes using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) to form particles of the mixed colorant dispersion. Thereafter, the internal temperature was rapidly cooled to 30° C. and maintained at that temperature for 12 hours to remove the solvent, thereby obtaining an aqueous medium in which resin particles were dispersed.

[0096] Hydrochloric acid was added to the aqueous medium in which the resin particles were dispersed to adjust the pH to 1.4, and the dispersant was dissolved by stirring for 1 hour. The dispersion was filtered using a pressure filter, and the obtained wet resin particles were washed to obtain a toner cake. The toner cake was then crushed and dried to obtain toner particles 23.

[0097] 0.5 parts of hydrophobic silica fine particles having a primary particle number average particle size of 20 nm and surface-treated with 25% by mass of hexamethyldisilazane were added to 100.0 parts of toner particles 23, and mixed in a Henschel mixer (FM-10 type manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 23. The temperature of the Henschel mixer was adjusted so that the temperature of the mixture was 30°C. The main formulation and manufacturing conditions of the toner 23 are shown in Table 4.

[0098] [Table 4] In the table, A is a hydrocarbon wax (melting point: the temperature at which the endothermic peak is at its maximum: 77°C). B represents behenyl behenate (melting point: 72° C.).

[0099] <Production Example of Toner 24-27> Toners 24 to 27 were obtained in the same manner as in the production example of Toner 23, except that the formulation and production conditions were changed as shown in Table 4.

[0100] <Toner 28 Manufacturing Example> Polyester resin 1 (resin B) 5.0 parts Styrene and n-butyl acrylate copolymer (Resin A) 100.0 parts (copolymerization mass ratio: styrene:n-butyl acrylate=72:28, peak molecular weight (Mp)=17000) Hydrocarbon wax (melting point: maximum endothermic peak temperature: 77℃) 14.0 copies 3,5-di-t-butylsalicylic acid aluminum compound 1.0 parts Carbon black 6.0 parts (Nipex35, Evonik Japan)

[0101] The above formulation was mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then melt-kneaded in a twin-screw kneader (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) set at a temperature of 120°C. The kneaded product obtained was cooled and coarsely crushed to 1 mm or less in a hammer mill to obtain a coarsely crushed product. The obtained coarsely crushed product was then crushed into resin particles using a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.).

[0102] [Spherical processing process] The obtained pulverized resin particles were subjected to a spheronization treatment using hot air at 280° C. in a surface modification machine, Meteor Rainbow (manufactured by Nippon Pneumatic Mfg. Co., Ltd.). Thereafter, classification was carried out using an air classifier (Elbow Jet PURO, Matsubo Corporation) to obtain toner particles 28.

[0103] 0.5 parts of hydrophobic silica fine particles having a primary particle number average particle size of 20 nm and surface-treated with 25% by mass of hexamethyldisilazane were added to 100.0 parts of toner particles 28, and mixed in a Henschel mixer (FM-10 type manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 28. The temperature of the Henschel mixer was adjusted so that the temperature of the mixture was 30°C. Here, the manufacturing conditions of the toner 28 are shown in Table 5.

[0104] [Table 5]

[0105] <Production example of toner 29-30> Toners 29 to 30 were obtained in the same manner as in the production example of Toner 28, except that the production conditions were changed as shown in Table 5.

[0106] <Toner 31 Manufacturing Example> Polyester resin 1 (resin B) 5.0 parts Styrene and n-butyl acrylate copolymer (Resin A) 100.0 parts (Copolymerization mass ratio: styrene: n-butyl acrylate = 72:28, peak molecular weight (Mp = 16000) Hydrocarbon wax (melting point: maximum endothermic peak temperature: 77℃) 14.0 copies 3,5-di-t-butylsalicylic acid aluminum compound 1.0 parts Carbon black 6.0 parts (Nipex35, Evonik Japan)

[0107] The above formulation was mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then melt-kneaded in a twin-screw kneader (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) set at a temperature of 120°C. The kneaded product obtained was cooled and coarsely crushed to 1 mm or less in a hammer mill to obtain a coarsely crushed product. The coarsely crushed product obtained was crushed twice in a mechanical crusher (T-250, manufactured by Turbo Kogyo Co., Ltd.) to obtain a resin particle crushed product.

[0108] [Spherical processing process] The obtained resin particle pulverized material was subjected to a spheronization process while being classified in a mechanical surface modification device (Faculty F-400 model, manufactured by Hosokawa Micron Corporation) by rotating the dispersion rotor with a stator at 12,000 rpm and the classification rotor at 6,000 rpm, thereby obtaining toner particles 31.

[0109] 0.5 parts of hydrophobic silica fine particles having a primary particle number average particle size of 20 nm and surface-treated with 25% by mass of hexamethyldisilazane were added to 100.0 parts of toner particles 31, and mixed in a Henschel mixer (FM-10 type manufactured by Mitsui Miike Chemical Engineering Co., Ltd.) to obtain toner 31. The temperature of the Henschel mixer was adjusted so that the temperature of the mixture was 30°C. Here, the manufacturing conditions of the toner 31 are shown in Table 6.

[0110] [Table 6]

[0111] <Production Example of Toner 32> Toner 32 was obtained in the same manner as in the production example of toner 31, except that the production conditions were changed as shown in Table 6.

[0112] <Toner 33 Manufacturing Example> (Preparation of aqueous medium) In a granulation tank, 100.0 parts of ion-exchanged water, 2.0 parts of sodium phosphate, and 0.9 parts of hydrochloric acid with a hydrogen chloride concentration of 10% by mass were added, and the mixture was heated and maintained at 50° C. To this, an aqueous calcium chloride solution in which 1.2 parts of calcium chloride hexahydrate were dissolved in 8.2 parts of ion-exchanged water was added. After the addition, the mixture was stirred for 30 minutes at a peripheral speed of 25 m / s using a TK homomixer (trade name, manufactured by Tokushu Kika Kogyo Co., Ltd.) to obtain an aqueous medium containing poorly water-soluble inorganic fine particles with a pH of 5.0.

[0113] (Preparation of Polymerizable Monomer Composition) (Preparation of Pigment Dispersion Composition) Styrene 39.0 parts Carbon black 6.5 parts (Nipex35, Evonik Japan) The above materials were introduced into an attritor (manufactured by Nippon Coke Corporation) and stirred at 200 rpm at 25° C. for 180 minutes using zirconia beads with a radius of 1.25 mm, and then the zirconia beads were removed to prepare a pigment dispersion composition.

[0114] (Preparation of Polymerizable Monomer Composition) The following materials were placed in a container and mixed and dispersed at a peripheral speed of 20 m / s using a TK homomixer (manufactured by Tokushu Kika Kogyo). Pigment dispersion composition 46.0 parts Styrene 31.0 parts n-Butyl acrylate 30.0 parts Polyester resin 5 2.0 parts Further, after heating to 60° C., 10.0 parts of behenyl behenate (melting point: temperature at which the endothermic peak is maximum: 72° C.) was added, and the mixture was dispersed and mixed for 30 minutes to obtain a polymerizable monomer composition.

[0115] <Process (I)> The polymerizable monomer composition was put into an aqueous medium containing poorly water-soluble inorganic fine particles, and stirred at a peripheral speed of 30 m / s with a TK homomixer (manufactured by Tokushu Kika Kogyo) under a nitrogen atmosphere at a temperature of 60° C. 6.0 parts of a polymerization initiator t-butyl peroxypivalate (manufactured by Nippon Oil & Fats Corporation, trade name "Perbutyl PV", molecular weight: 202, 10-hour half-life temperature: 53.2° C.) was dissolved in the mixture to prepare a polymerizable monomer composition containing the polymerization initiator.

[0116] <Process (II)> The dispersion containing the particles of the polymerizable monomer composition was transferred to another tank, and the temperature was raised to 70°C while stirring with a paddle stirring blade, and the polymerizable monomer contained in the particles of the polymerizable monomer composition was polymerized for 6 hours. Thereafter, the temperature was further raised to 80°C and reacted for 6 hours to form resin particles. At this time, the pH of the polymerization slurry was 5.0. Then, aluminum chloride was added at 80°C to a concentration of 2.0 mmol / L, and the mixture was stirred for another 2 hours under the same conditions.

[0117] <Distillation process> After the polymerization step was completed, steam at 120°C was started to be fed to the slurry containing the aqueous medium and the resin particles at a flow rate of 30.0 parts / hr. After the start of the steam feed, distillation was started when the temperature reached 98°C, and distillation was continued for 8 hours.

[0118] <Process (III)> After the distillation step, a 7.0% aqueous solution of sodium carbonate was added to the slurry containing the aqueous medium and the resin particles so that the pH of the aqueous medium became 8.0, and the slurry was then kept at 80° C. for 30 minutes.

[0119] <Washing, filtering, drying, and classification processes> After the step (III) was completed, the mixture was cooled, hydrochloric acid was added to adjust the pH to 1.4, and the mixture was stirred for 2 hours to obtain an aqueous dispersion containing toner particles. The toner particles were filtered out from the aqueous dispersion, washed with water, dried at 40° C. for 48 hours, and classified to obtain toner particles 33.

[0120] <External addition process> The external addition step was carried out in the same manner as in the production example of toner 1.

[0121] The physical properties of Toners 1 to 33 are shown in Table 7 below.

[0122] [Table 7]

[0123] <Example 1> The above toner 1 was used to carry out the following evaluations. For the evaluation, a commercially available color laser printer [HP Color LaserJet Enterprise M855] was used with some modifications. The modifications were as follows: (1) It is now possible to operate the printer with just one color toner cartridge and imaging drum installed. (2) The process speed was set to 55 ppm. (3) The fixing unit temperature can be changed to any desired temperature. (4) By changing the gears around the developing roller and toner supply roller of the imaging drum, the rotation directions of the developing roller and toner supply roller have been changed from being in the same direction to being in opposite directions. The toner in the black toner cartridge and imaging drum mounted on this color laser printer was removed, the inside was cleaned with an air blower, and then toner 1 (425 g) was introduced into the toner cartridge and toner 1 (127 g) was introduced into the imaging drum, and the toner cartridge and imaging drum refilled with toner were installed in the color laser printer and the following evaluations were carried out. The specific image evaluation items are as follows:

[0124] <Image fogging> In a low temperature and low humidity environment (temperature 15°C, humidity 10% RH) and a high temperature and high humidity environment (temperature 33°C, humidity 85% RH), 30,000 sheets of horizontal line images with a printing rate of 1% were printed out and then left for 48 hours. Thereafter, the reflectance (%) of the non-image portion of one further printed image was measured using a "REFLECTOMETER MODEL TC-6DS" (manufactured by Tokyo Denshoku Co., Ltd.). The reflectance thus obtained was subtracted from the reflectance (%) of an unused printout paper (standard paper) measured in the same manner, and the value (%) was used to evaluate the reflectance according to the following evaluation criteria. The smaller the value, the more the image fog is suppressed. The evaluation was performed in gloss paper mode using plain paper (HP Brochure Paper 200g, Glossy, manufactured by HP, 200g / m 2 ) was used. (Evaluation Criteria) A: Less than 0.5% B: 0.5% or more but less than 1.5% C: 1.5% or more and less than 3.0% D: 3.0% or more

[0125] <Component contamination> In a high temperature and humidity environment (temperature 33°C, humidity 85% RH), a halftone image was initially output and it was confirmed that there were no uneven shadings on the image. After that, 50,000 sheets of an image with a vertical line and a print rate of 30% were printed out. In addition, when the toner cartridge ran out of capacity, a new toner cartridge was inserted and the test was carried out. After printing out 50,000 sheets, a halftone image was output and visually observed to see whether or not there was unevenness in density between the printed image area and the non-printed image area on the halftone image. Thereafter, the developing blade was removed, the toner at the contact portion between the developing roller and the developing blade was blown off with air, and the developing blade was observed. The results of the observation were evaluated according to the following evaluation criteria. (Evaluation Criteria) A: There is no unevenness in the image density, and the developing blade is in good condition. B: No unevenness in density was observed on the image, but some filming was observed on the developing blade. C: Slight unevenness in the image D: Unsightly uneven shading on the image

[0126] <Fine line reproducibility> The thin line reproducibility was evaluated in a normal temperature and humidity environment (temperature 25°C, humidity 50% RH). After printing out 20,000 images with vertical lines at a printing rate of 30%, an image with a grid pattern with a line width of 3 pixels printed across the entire surface of an A4 sheet of paper (printing area rate of 4%) was printed, and the fine line reproducibility was evaluated using the following evaluation criteria. The theoretical line width of 3 pixels is 127 μm. The line width of the image was measured using a microscope VK-8500 (product name, manufactured by Keyence). Five points were randomly selected to measure the line width, and the average value of the three points excluding the minimum and maximum values ​​was taken as d (μm). The thin line reproducibility index L was calculated and evaluated according to the following evaluation criteria. L(μm)=|127-d| L defines the difference between the theoretical line width of 127 μm and the line width d on the output image. Since d can be greater or less than 127, it is defined as the absolute value of the difference. The smaller the value of L, the better the thin-line reproducibility. (Evaluation Criteria) A: L is 0 μm or more and less than 5 μm B: L is 5 μm or more and less than 15 μm, and slight variation in the width of the fine line is observed. C:L is 15μm or more and less than 30μm, and thinning and scattering of fine lines are observed, but it is still usable. D:L is 30μm or more, and thin wires are broken or thickened in places. The results of Example 1 are shown in Table 8. As shown in Table 8, the results of Example 1 were all good.

[0127] <Examples 2 to 1 5 > Except for changing Toner 1 to each toner shown in Table 8, evaluation was performed in the same manner as for Toner 1. Examples 8 and 11 to 15 were evaluated as reference examples. The evaluation results are shown in Table 8.

[0128] <Comparative Examples 1 to 18> Except for changing Toner 1 to each toner shown in Table 8, evaluation was performed in the same manner as for Toner 1. The evaluation results are shown in Table 8.

[0129] [Table 8] [Explanation of symbols]

[0130] 1: Resin B, 2: Resin A

Claims

1. A toner having toner particles containing a binder resin, The binder resin contains resin A and resin B, The resin A contains a styrene (meth)acrylic resin, The resin B contains a polyester resin, The acid value of the resin B is 14 mgKOH / g or more and 20 mgKOH / g or less, the toner particles have convex portions on their surfaces, The convex portion contains the resin B, the toner has a shape factor SF-2 observed by a scanning electron microscope of 105 to 120; The toner is characterized in that the surface unevenness index of the toner, which is calculated by the following formula (1) when observed with a scanning electron microscope, is 0.010 to 0.050: Surface roughness index=(area of ​​region surrounded by convex hull of toner−projected area of ​​toner) / projected area of ​​toner (1)

2. 2. The toner according to claim 1, wherein the toner has a shape factor SF-1 of 105 or more and 120 or less as observed by a scanning electron microscope.

3. 3. The toner according to claim 1, wherein the standard deviation of the surface unevenness index of the toner is 0.010 or less.

4. 4. The toner according to claim 1, wherein the content of the polyester resin relative to 100.0 parts by mass of the resin A is 3.0 parts by mass or more and 15.0 parts by mass or less.

5. the toner particles contain a wax, In a cross section of the toner observed with a transmission electron microscope, The percentage of the area occupied by the wax in the region surrounded by the contour of the toner and a line 1.0 μm away from the contour toward the inside of the toner is defined as As, When the percentage of the area occupied by the wax present in the inner region inside a line 1.0 μm away from the contour of the toner toward the inside of the toner is Ac, The compound according to any one of claims 1 to 4, wherein As and Ac satisfy the following formula (2): Yeah. 50.0≧[As / (Ac+As)]×100≧3.0 (2) 6. The toner according to claim 1, wherein the polyester resin has an acid dissociation constant pKa of less than 6.

5.

7. A method for producing the toner according to any one of claims 1 to 6, comprising the steps of: The manufacturing method comprises: A step (I) of forming particles of a polymerizable monomer composition containing a polymerizable monomer capable of forming the resin A and the resin B in an aqueous medium; a step (II) of polymerizing the polymerizable monomer contained in the particles of the polymerizable monomer composition in the aqueous medium to form resin particles; and (III) a step of maintaining the resin particles in an aqueous medium having a pH higher than the acid dissociation constant pKa of the resin B at a temperature equal to or higher than the glass transition temperature of the resin B; A method for producing a toner comprising the steps of:

8. 8. The method for producing a toner according to claim 7, wherein in the step (III), the resin particles are held in an aqueous medium having a pH higher than the acid dissociation constant pKa of the resin B at a temperature equal to or higher than the glass transition temperature of the resin B for 30 minutes or more.

9. The method for producing a toner according to claim 7 or 8, wherein a content of the polyester resin relative to 100.0 parts by mass of the polymerizable monomer capable of forming the resin A is 3.0 parts by mass or more and 15.0 parts by mass or less.

10. In the step (III), the aqueous medium has a pH of 6.5 to 10.0; The method for producing a toner according to any one of claims 7 to 9, wherein the polyester resin has an acid dissociation constant pKa of less than 6.5.

Citation Information

Patent Citations

  • Toner, its production and image forming method

    JP2001013732A

  • Image forming device

    JP2001147549A

  • Light fixable toner, two-component developer and method for producing light fixable toner

    JP2011197160A

  • Toner, developer and image forming method

    JP2012189868A

  • Toner, developer, and image forming method

    JP2013064965A